(untitled) (Al-Qamar, 2023)
From the very beginning, scholars have arranged the miracles of Quran sometimes in terms of its coherence and sometimes in terms of llm ul Munasabat. Every chapter of the Holy Quran has a basic theme around which revolves all its verses and some of the scholars of later times have explained them. Moreover, scholars have managed to demonstrate the topics of verses of Quran and basic theme around which every verse revolves around among other verses, so that they could reach its thematic unity/objective unity which gathers all verses of Quran and its chapters entirely. Owing of its importance in the understanding of Quran, some of the scholars have tried hard to show this dimension of Quran. Among these scholars, Ubaidullah Sindhi has written llham-ur-Rahman in Arabic while Hussain-al-Wani and Dr. Israr has written Bulghat ul Hairan and Bayan-ul Quran in Urdu respectively. Each one of them has their own particular opinion about Wahdat-ul-Mozoia (Thematic unity). I have chosen these aforementioned interpretations of Quran in which I will compare their thoughts about Wahdat-ul-Mozoia.